Control interno de los egresos en el departamento administrativo-financiero de la Fiscalía Provincial de Los Ríos - Arellano Tumailla, Laura Karina (2020)
The institution to which reference will be made is the Los Ríos Provincial Prosecutor's Office in which this case study was carried out with the topic: Internal Control in the expenditures of the administrative-financial department of the Los Ríos Provincial Prosecutor's Office, the sub-line Research is as follows: Audit and control, which is related to the Engineering in Accounting and Auditing Career of the Faculty of Administration. The Los Ríos Provincial Prosecutor's Office is a body that is in charge of clarifying cases of corruption, promotes the exercise of justice for the benefit of citizens, focusing with transparency and fighting against impunity, it is a public sector entity, it is regulated by the Comptroller General of the State, the government grants an annual budget to carry out operational activities. The investigation was conducted with the purpose of evaluating compliance with the rules, regulations, and other statutes related to the internal control of expenditure budgets for public sector institutions. The internal control itself is oriented to the legal, technical and administrative system with which it is sought to conclude the activities of the budget plan in an efficient and effective way, providing reliability in the presentation of accounting information. In itself, it is a process that must be developed linked to the legal provisions and regulations determined by the highest authority or the person in charge of the institution. Taking into account that it must be based on the Internal Control Standards of the State Comptroller General's Office.